Between Love and Faith: Interfaith Marriage from the Perspective of Sayyid Qutb - Selfi Lutfa Utami; Luna Ashma Nabila (Studia Quranika, 2025)
This study discusses the ruling on interfaith marriage according to the Qur’an, particularly in Surah al-Baqarah verse 221. This verse explicitly prohibits marriage between a Muslim and a polytheist due to its potential negative impact on faith. Sayyid Qutb, in his tafsir Fī Ẓilāl al-Qur’ān, emphasizes the importance of preserving religious beliefs and spiritual values within the family, and warns against the dangers of interfaith marriage. Although Islam permits marriage with the People of the Book under certain conditions, it still requires safeguarding one’s faith. This research aims to examine the relationship between love and faith in the context of interfaith marriage based on the interpretation of Q.S. al-Baqarah: 221. The study employs a qualitative method with a thematic (maudhu’i) approach, specifically using the adab al-ijtimā‘i interpretation model. It is a library-based research using descriptive-analytical techniques. The findings reveal that interfaith marriage is prohibited in Islam, as marriage is not merely the union of two individuals, but a means of perfecting the faith of Muslim men and women. This research is expected to serve as a reference for further studies in the field of Qur’anic exegesis.